(untitled) (University Heart Journal, 2009)
This prospective observational study was done in National Institute of Cardiovascular Diseases and hospital Dhaka, during the period April 2002 to July 2008. In this study the immediate results of balloon mitral valvuloplasty with mitral restenosis patients with previous surgical mitral commissurotomy was evaluated. We have done 50 cases of percutaneous balloon mitral valvuloplasty in patients who had the history of previous surgical commissurotomy. Out of these 50 patients 8 patients were male and 42 patients were female. The age range was 25-55 years with duration of surgical commissurotomy (SC) of 2-18 years past. The result of balloon mitral valvuloplasty (BMV) was successful in 48 cases and failed in 2 cases due to huge left atrium, balloon did not negotiate from LA to LV. Mitral valve area (MVA) before the procedure was 0.5-0.9 sq cm with mean 0.7± 2 sq cm. Following procedure the MVA was 1.6-2.04 cm2 with a mean of 1.8±0.2 cm2. Gradient across mitral valve (MV) before and after the procedure was 20-44 mm Hg with a mean of 32±-12 mm Hg and 8-12 mmHg with a mean of 10±2 mm Hg. MVA >1.8 cm2 was achieved in 41 cases &1.8-1.6 cm2 in 7 cases. Mitral regurgitation >1 grade occurred in 8 cases. So we conclude that BMV in patients with mitral restenosis following SC can be performed successfully with low risk of major cardiac complications. Key words: Surgical commissurotomy (SC), balloon mitral valvuloplasty (BMV) doi: 10.3329/uhj.v5i1.3433 University Heart Journal Vol. 5, No. 1, January 2009 9-12